PENGGUNAAN MEDIA CERITA BERGAMBAR TERHADAP HASIL BELAJAR SISWA PADA MATERI IPS KELAS III SEKOLAH DASAR - Wahyudi Saputra; Aramudin, Aramudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research has a purpose to know whether there is influence to result of student learning in usage of pictorial story media compared with conventional learning at social study material. This research uses quantitative research method with experimental type and has noquivalent control design. The population of this study is the third grade students of and the samples used are saturated sampling. The data required from this research is the result of student learning from multiple choice questions in the form of post test and pre test. Data were analyzed using descriptive statistic using SPSS version 20 data processing program. The results showed a significant differences on student learning result from N-gain value in experimental class 0,682 (medium) while in control class 0,389 (low). This research has average value in experiment class that is pre test equal to 65,48 post test equal to 89,03, while in control class that is pre test equal to 65,16 post test equal to 78,71. This proves influence on student learning outcomes using pictorial story media that have been applied in the experimental class.